Awareness of Consequences Sustainable Development Goals (SDGS) on Pro-Environmental Behavior of Student Activity Boards - Gufron Amirullah; Eva Marthinu; Irdalisa Irdalisa; Arief Nurdiyantono (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine whether there is an influence of Awareness of the Consequences of Sustainable Development Goals (SDGs) on Pro-Environmental Behavior in Student Activity Boards. The research method used is a correlational quantitative research method with an instrument distribution research design. The sample used is purposive sampling. In the validity test using the Product Moment correlation formula, there are 40 statement questions with 31 valid questions and 9 invalid questions. While the reliability test using calculations from SPSS obtained recount = 0.95 so that the level of reliability is high. Furthermore, the data were analyzed using the normality test using the Kolmogorov-Smirnov test with the provisions of Probability < P-value 0.05, variable X obtained 0.20 < 0.05, and variable Y 0.06 < 0.05, it can be concluded that the data is normally distributed. Meanwhile, the linearity test using the Sig test obtained a significance of 0.17 < P-value 0.05, it can be concluded that both data are linear. Based on the research results, it can be concluded that there is a positive influence of Awareness of the Consequences of Sustainable Development Goals (SDGs) on Pro-Environmental Behavior in student family activists.